Students' Beliefs and Strategies In The Use Of Translation In Learning English - Fahrezi, M. Gusti; Oktavia, Witri (Journal of English Language Teaching, 2024)
The purpose of this research was to find out what strategies the students use in employing translation and what are they beliefs  about the use of translation in learning English. The subject of this research was students of class K6 from the academic year 2022 at Universitas Negeri Padang. This research was conducted using quantitative methods, using a questionnaire adapted from Ahmad Muzdalifah (2016) as an instrument of data collection. The result of this research shows that the students believe in the use of translation help them with the English skills such as reading, writing, speaking and use strategies for using translation in learning English for reading and speaking. According to the findings, students positively believe in the use of translation as a strategy made extensive use of it when they were studying in their learning process.